Law Enforcement On Distributors Who Retail Goods To Consumers In The MSMEs Sector - Livia, Stella; Haryanto, Imam (Faculty of Law, Universitas Negeri Semarang, 2021)
Distributors and retailers have a relationship in running their business. Their relationship creates business competition. Business competition is legitimated as long as it does not break the existing regulations. Distributors retail goods to consumers, it has a detrimental impact on retail traders. It requires a more in-depth study related to business competition law reviews about this case, especially on analyzing the existence of unfair business competition and seeking legal certainty for law enforcement. Relates to distributors who direct retail their goods to consumers. This research method use in this research was juridical normative, which uses a statutory approach with secondary data sources. There are indications of abuse of dominant position related to monopolize the market. It is regulated in Law Number 5 of 1999 concerning Monopolistic Practices and Unfair Business Competition against the distributor's actions. That action is regulated on Number 22 of 2016 concerning General Provisions of trade minister for the Distribution of Goods which prohibits the distributor who retails their product to consumers clearly and the sanctions. Therefore, law enforcement is carried out based on the provisions of these regulations.